PEMAHAMAN GURU BIOLOGI SMA KOTA SURAKARTA TERHADAP HAKIKAT BIOLOGI SEBAGAI SAINS - Bowo Sugiharto (Universitas Sebelas Maret, 2014)
This study aims to describe the understanding of senior high school biology teacher of Surakarta against the nature of biology as science. The value of understanding of the nature of biology as science was taken form the test. This study was conducted in April 2014. The sample used was 36 biology teachers that is incorated in MGMP Biologi SMA Surakarta. The results showed that average of the understanding is 2,32 that is classified in C with the standard deviation of 0.42. Overall value of understanding distributed into A as much as 0 (0%), A- as much as 0 (0%), B+ as much as 1 (2.78%), B as much as 1 (2.78%), B- as much as 18 (50%), C+ as much as 10 (27,78%), C as much as 4 (11.11%), C-as much as 0 (0%), D as much as 1 (2.78%), and D as much as 1 (2.78%). Keywords: biology teacher, the nature of biology as science